Pengembangan Animasi 3d “Kesuba” Untuk Meningkatkan Hasil Belajar Dan Nilai Karakter Peserta Didik Kelas IV MI Bahrul Ulum Surabaya - Atika Dwi Rahmawati; Muhammad Turhan Yani; Raden Roro Nanik Setyowati (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study is to determine the feasibility, practicality and effectiveness of 3D animation products in improving learning outcomes and internalizing character values. The subject of the device trial was carried out on students of Madrasah Ibtidaiyah Bahrul Ulum Surabaya. Research design using Pre-Experimental. The form is in the form of a One-Shot Case Study. In this design there is a group given treatment and observed (Q). Data collection techniques in this study used tests, observations, interviews and questionnaires. So the conclusion of this study is that the development of animated media in learning material on ethnic and cultural diversity in the classroom can provide alternative interactive media. There is an increase in the use of animated media in learning material on ethnic and cultural diversity. The use of animation media on ethnic and cultural diversity material provides maximum completeness value.